Insulin resistance is a cause of steatosis and fibrosis progression in chronic hepatitis C. Issue 7 (10th June 2005) - Fartoux, L; Poujol-Robert, A; Guéchot, J; Wendum, D; Poupon, R; Serfaty, L
Abstract : Background: Insulin resistance is a frequent feature of chronic hepatitis C. Whether insulin resistance could be the cause or consequence of steatosis and fibrosis is unknown. The ability of HCV genotype 3 to promote steatosis by itself provides an unique opportunity to answer this question. Aims: The aim of the present study was to assess the relationships between insulin resistance, steatosis, and fibrosis according to genotype in 141 non-diabetic patients with biopsy proven non-cirrhotic chronic hepatitis C. Methods: All patients had fasting serum glycaemia and insulinaemia measurements. Insulin resistance was evaluated using the homeostasis model assessment (HOMA IR) method. Liver steatosis was determined according to hepatitis C virus genotype (1 or 3). Logistic regression and multivariate regression analysis were used to identify variables independently associated with insulin resistance, fatty liver, and fibrosis. Results: Although steatosis and fibrosis were more severe in genotype 3 patients, median HOMA IR was significantly higher in patients with genotype 1 related steatosis than in those with genotype 3 related steatosis (2.1 v 1; p = 0.001). Independent risk factors for steatosis were insulin resistance in genotype 1 patients (p = 0.001) and viral load in genotype 3 patients (p = 0.003). Among genotype 1 patients, independent parameters associated with insulin resistance were age (p = 0.04) and steatosis (p = 0.004). Steatosis was associated with more severe fibrosis whatever the genotype (p = 0.002). Among genotype 1 patients, although there was a significant relationship between circulating insulin level and fibrosis stage (p = 0.006), only steatosis and inflammatory score were independently associated with fibrosis. Conclusion: This study shows that insulin resistance is the cause rather than the consequence of steatosis and fibrosis in genotype 1 patients and that increased circulating insulin is a risk factor for fibrosis through insulin resistance induced steatosis.